PENGAKUAN HAK-HAK PEREMPUAN SEBAGAI PEKERJA RUMAH TANGGA (Domestic Workers) SEBAGAI BENTUK PERLINDUNGAN HUKUM MENURUT HUKUM POSITIF INDONESIA - Turatmiyah, Sri; Y., Annalisa (Jurnal Dinamika Hukum, 2013)
Many offences to domestic workers’ rights. The research on the legal protection of women as domestic workers (PRT) in Indonesian positive law is intended to allow the legitimacy of women’s rights recognition and protection as domestic workers especially in Employment Act which is being revised/amended at this time. The research was carried out by normative juridical approach. The results showed that the recognition of the rights of women as domestic workers has not specifically stipulated in the Act, given their status as workers in the informal sector, the sector is not organized (unorganized), not regulated (unregulated) and mostly legal but not registered (unregistered). The efforts of the law regarding women as domestic workers concerning their rights to use legislation such as the Constitution, Law No 39, year 1999 about human Rights, Law no. 23 year 2004 (about domestic violence), and part of Law no. 13 of 2003 on Manpower/employment. The government is expected to approve and establish the Law on the Protection of domestic workers.Key words: domestic workers, protection laws, informal sector